Architectural Style of Riverside Settlements in Banjarmasin City - afdholy, Amar rizqi; Wulandari, Lisa Dwi; Utami, Sri (University of Merdeka Malang, 2019)
Riverside settlements in Banjarmasin City can be classified as a part of vernacular architecture, this classification was made by the initial researchers. This classification underlying the research about architecture style in one of the riverside settlements in Banjarmasin City which still has strong riverside culture, the focus point of this research is at the riverside settlements of Bromo Island Delta, Mantuil, Banjar Selatan subdistrict, Banjarmasin City. The determination of this assessments refers to vernacular architecture style using a qualitative research method and purposive sampling technique. From 25 samples, we found 2 styles of architecture on the riverside settlements in Bromo Island Delta. They are vernacular architecture and semi vernacular architecture style. Addition of space function, the change of foundation structure and material, economy and community knowledge about recent technology are the development factors of vernacular houses changes into semi vernacular houses.Â DOI: https://doi.org/10.26905/lw.v11i2.2961